Evaluating Computer Capabilities in a Primary Care Practice-Based Research Network - Ariza, Adolfo J. (Copyright 2004 Annals of Family Medicine, Inc., 2004)
PURPOSE We wanted to assess computer capabilities in a primary care practice-based research network and to understand how receptive the practices were to new ideas for automation of practice activities and research. METHOD This study was conducted among members of the Pediatric Practice Research Group (PPRG). A survey to assess computer capabilities was developed to explore hardware types, software programs, Internet connectivity and data transmission; views on privacy and security; and receptivity to future electronic data collection approaches. RESULTS Of the 40 PPRG practices participating in the study during the autumn of 2001, all used IBM-compatible systems. Of these, 45% used stand-alone desktops, 40% had networked desktops, and approximately 15% used laptops and minicomputers. A variety of software packages were used, with most practices (82%) having software for some aspect of patient care documentation, patient accounting (90%), business support (60%), and management reports and analysis (97%). The main obstacles to expanding use of computers in patient care were insufficient staff training (63%) and privacy concerns (82%). If provided with training and support, most practices indicated they were willing to consider an array of electronic data collection options for practice-based research activities. CONCLUSIONS There is wide variability in hardware and software use in the pediatric practice setting. Implementing electronic data collection in the PPRG would require a substantial start-up effort and ongoing training and support at the practice site.